Boom-Bust Cycles in Middle Income Countries: Facts and Explanation - Aaron Tornell; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2002)
In this paper we characterize empirically the comovements of macro variables typically observed in middle income countries, as well as the boom-bust cycle' that has been observed during the last two decades. We find that many countries that have liberalized their financial markets, have witnessed the development of lending booms. Most of the time the boom gradually decelerates. But sometimes the boom ends in twin currency and banking crises, and is followed by a protracted credit crunch that outlives a short-lived recession. We also find that during lending booms there is a real appreciation and the nontradables (N) sector grows faster than the tradables (T) sector. Meanwhile, the opposite is true in the aftermath of crisis. We argue that these comovements are generated by the interaction of two characteristics of financing typical of middle income countries: risky currency mismatch and asymmetric financing opportunities across the N- and T-sectors.
Keywords: 330